The Challenges for Court Reform after Authoritarian Rule: The Role of Specialized Courts in Indonesia - Melissa Crouch (Constitutional Review, 2021)
Political transitions from authoritarian rule may lead to a process of court reform. Indeed, court reform has been a central pillar of the law and development movement since the 1960s. What challenges do court reform efforts face after authoritarian rule in Indonesia and to what extent can specialized courts address these challenges? In this article, I examine court reform and the establishment of specialized courts in Indonesia post-1998. I argue that we need to pay attention to the politics of court reform after authoritarian rule. Specialized courts as a type of institutional reform need to be considered together with judicial culture in order to address fundamental challenges in the courts.